Investigation of the Dominant Microbiota in Ready-to-Eat Grasshoppers and Mealworms and Quantification of Carbapenem Resistance Genes by qPCR - Milanović, Vesna; Osimani, Andrea; Roncolini, Andrea; Garofalo, Cristiana; Aquilanti, Lucia; Pasquini, Marina; Tavoletti, Stefano; Vignaroli, Carla; Canonico, Laura; Ciani, Maurizio; Clementi, Francesca (Frontiers in Microbiology, 2018)
In this study, thirty samples of processed edible mealworms (Tenebrio molitor L.) and thirty samples of grasshoppers (Locusta migratoria migratorioides) were obtained from producers located in Europe (Belgium and the Netherlands) and Asia (Thailand) and subjected to PCR-DGGE analyses. The PCR-DGGE analyses showed that species in the genus Staphylococcus were predominant in the samples of mealworms from Belgium and grasshoppers from the Netherlands; species in the genus Bacillus were detected in the samples of mealworms and grasshoppers from Thailand. Moreover, Weissella cibaria/confusa/sp. was found in grasshoppers from Belgium. Since, data concerning the role of novel foods such as edible insects in the dissemination of carbapenem resistance are currently lacking, the quantification of five carbapenemase encoding genes (blaNDM-1, blaVIM-1, blaGES-1, blaOXA-48, and blaKPC) using qPCR method was also carried out in all the samples under study. The genes coding for GES-1 and KPC were not detected in the analyzed samples. A very low frequency of blaOXA-48 (3%) and blaNDM-1 (10%) genes was detected among the mealworm samples. In contrast, grasshoppers were characterized by a high incidence of the genes for OXA-48 and NDM-1, accounting for 57% and 27% of the overall grasshopper samples, respectively. The blaVIM-1 gene was detected exclusively in two grasshopper samples from Thailand, showing only 7% positivity. The analysis of variance showed that all the effects (producers, species, and producers x species) were statistically significant for blaNDM-1, whereas for blaOXA-48 and blaVIM-1, no significant effects were detected for the same source of variation. Further studies are necessary to assess the possible role of edible insects as reservoirs for the resistance to carbapenems and to understand the correlation with the insect microbiota. Furthermore, an intensified surveillance plan examining the occurrence of carbapenemase encoding genes in the food chain and in environmental compartments is needed for a proper risk assessment. In such a context, the appropriate use of antimicrobials represents the main preventive action that should always be applied.